Efektivitas Model Stringer “Look Think Act” Terhadap Kualitas Hidup Wanita Rawan Sosial Ekonomi di Bogor - Dedes Fitria; Titi Nurhayati, (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Background: The Life of Women with Socio-Economic Vulnerability (WRSE) in the Ministry of Social Affairs' Profile of Vulnerable Women (WRSE) and the Indonesian Central Statistics Agency in 2010 are classified as poor (living below the poverty line) Empowerment of women as a continuous process to improve The ability and independence of poor women in poverty alleviation through entrepreneurship training that provides knowledge, attitudes, skills that can make them independent and can improve their quality of life. Purpose: This study aims to determine the effectiveness of the Stringer Look Think Act Model on the quality of life of socially vulnerable women in Bogor. The research design used action research research design with sequential explanatory mixed methods. Data collection and qualitative data analysis in the first stage, followed by quantitative data collection in the second stage to strengthen the research results. The sampling technique used was snowball. Variables were measured by questionnaires and interviews. Data analysis used the chi square test. Results: The implementation of the stringer look, think, act model is effective on the quality of life of women who are prone to socioeconomic conditions, which are obtained by the value of look (r = 0.009), think (r = 0.000) and act (r-0.000). Suggestion: Application of the Stringer Look Think Act model approach in approaching women who are vulnerable to socioeconomic age at productive ages as an effort to explore problems and increase knowledge and quality of life